Characterization and expression of cathepsin B2 in Fasciola gigantica - Chantree P. (2014)
Fasciola gigantica cathepsin B belongs to a family of cysteine proteases which is involved in invasion of host tissues. In this study, the recombinant cathepsin B2 (rFgCatB2), synthesized in Pichia pastoris, showed enzymatic activity on a fluorometric substrate Z-Phe-Arg-AMC and gelatin. Furthermore, this recombinant enzyme could degrade IgG and type I collagen. Mouse antiserum against rFgCatB2 reacted with the native FgCatB2 in whole body (WB) extracts of metacercariae (MET), newly excysted juveniles (NEJ) and 2. week-old juveniles, but not in 3, 4. week-old juveniles and adult flukes. Immunolocalization showed the presence of cathepsin B2 only in the caecal epithelium of MET, NEJ and 2. week-old juveniles. Co-localization of FgCatB2 and a prominent antigen of NEJ, FgCatB3, revealed that these proteins were expressed at the same regions in the caecal epithelium. Anti-rFgCatB2 showed no cross reaction with the other parasites' antigens by Western blotting. These findings suggest that CatB2 is expressed only in early stages of the parasite and may be involved in digestion of host connective tissues and evasion of the host immune system during their penetration and migration. Thus, CatB2 could be considered as an immunodiagnostic and vaccine candidate for fasciolosis. © 2012 Elsevier Inc.